Perawatan Ortodontik Gigitan Terbuka Anterior - Yuniar Zen (Faculty of Dentistry, Universitas Gadjah Mada, 2014)
Orthodontic Treatment of Anterior Open Bite. An anterior open bite therapy has long been considered a challenge to orthodontist. The prevalence of anterior openbite range from 3,5 % to 11% among various age and ethnic groups and it has been shown that approximately 17% of orthodontic patients have open bite. Stability of treatment result of anterior open bite with well-maintained results is difficult, because the combination of anteroposteriorly discrepancy with skeletal open bite requires the highest degree of diagnostic and clinical skill. The etiology is complex, potentially involving skeletal, dental and habitual factors. The importance of an anterior open bite therapy is to eliminate the cause of the open bite. Various treatment modalities for the correction of an anterior open bite have been proposed, orthognatic surgery and orthodontic camouflage treatment such as high-pull headgear, chin cup, bite blocks, functional appliances, extractions, multi-loop edgewise arch wires and mini implant. The stability is the most important criterion in deciding the treatment method for anterior open bite malocclusion.